Archaeology of the African Slaves in the Amazon. (3rd May 2016) - Costa, Diogo M.
Abstract : Many studies have been conducted on the history of Africans and their descendants in Brazil, but the potential of historical archaeology sites in the Amazon region has been little explored. I present a brief overview of this research, beginning with contemporary studies on African slavery and diaspora in Brazil, investigations combining history and archaeology in Brazil, and studies focused on the history and anthropology of the Amazon region. This article concludes with a case study of a systematic excavation of a slave quarter in the Brazilian Amazon, the Murutucu Sugar Cane Mill, in the vicinity of Belém city in Pará state in Brazil, and potential interpretations of the material culture remains uncovered at that site.